Strain decoupling reveals variable seismogenic risk in SE Japan (Nankai Trough). (1st July 2015) - Van Tuyl, James; Alves, Tiago M.; Moore, Gregory F.
Abstract The determination of in situ stress states is vital in understanding the behavior of faults and subsequent seismogenesis of accretionary prisms. In this paper, a high‐quality 3‐D seismic volume is used to map the depth of the extensional‐compressional decoupling (ECD) boundary in the accretionary prism of Nankai, with the prior knowledge that strike‐slip and compressional stresses occur deeper than 1250 m below seafloor (mbsf) in the Kumano Basin, changing to extension toward the seafloor. A total of 1108 faults from the accretionary prism are analyzed to estimate paleostresses via fault inversion and slip tendency techniques. A key result in this paper is that the ECD boundary can be used as a proxy to identify active structures on accretionary prisms as its depth depends on (a) local tectonic uplift in areas adjacent to active faults and (b) the thickness of sediment accumulated above active thrust anticlines. The depth of the ECD boundary ranges from 0 to ∼650 mbsf, being notably shallower than in the Kumano Basin. In Nankai, frontal regions of the imbricate‐thrust zone, and the megasplay fault zone, reveal the shallower ECD depths and correlate with the regions where faulting is most active. As a corollary, this work confirms that estimates of stress state variability based on the analysis of 3‐D seismic data are vital to understand the behavior of faults and potential seismogenic regions on convergent margins.